Design and optimization of industrial woody biomass pretreatment addressed by DryKiln_CRP, a multiscale computational model: Particle, bed, and dryer levels. Issue 15 (17th November 2016) - Colin, J.; Rémond, R.; Perré, P.
ABSTRACT: Thermochemical conversion processes of biomass to energy are increasingly demanding in terms of the quality of the raw material, especially regarding its moisture content. The use of continuous dryers is attractive because of their low cost and ease of integration into the production line. However, the design of the drier (drying chamber and heating source) and the optimization of its control based on relevant criteria are complex. This paper presents DryKiln_CRP, a comprehensive multiscale model able to account for the two-way interactions between particles, bed, and drier. The drying model at the particle level is based on the van Meel approach which was extended to account explicitly for heat and mass transfer coupling. Computational simulations are discussed for two case studies to emphasize the potential of this multiscale computational model in the design and optimization of industrial plants devoted to the pretreatment of biomass.